Economics Learning Outcomes of Jambi University Students Given Financial Literacy Analysis and Consumptive Behavior - Rosmiati Rosmiati; Zuhri Saputra Hutabarat (STAI Hubbulwathan Duri, 2023)
In part and concurrently, this study intends to ascertain the economic literacy, learning results, and consumption habits of students majoring in economics education at Jambi University. Regression analysis was used to examine this quantitative study. 101 members of Jambi University's 2019 Economics Education major class served as the research subjects. Using surveys and documentation, research data was gathered, and SPSS was used to process it. The analysis's findings indicate that: 1) College students lack excitement for saving, and their excessive spending habits make it challenging for them to be wise consumers. 2) The learning outcomes attained in economic learning may be used to gauge a person's capacity to identify sensible economic activities or non-consumptive conduct. 3) Students' consumption behavior decreases when economic literacy and student learning results go up, and vice versa. According to this research, children should better comprehend economic literacy, learning objectives, and consumptive behaviour. According to the findings of this study, economic literacy and learning outcomes have a negative and substantial impact on students majoring in economics at the University of Jambi.